2022
DOI: 10.3390/plants11101313
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of Useful Plants in Cabo Verde Islands: A Biogeographic and Conservation Perspective

Abstract: Cabo Verde’s biodiversity is threatened by activities that meet human needs. To counteract this, an integration of scientific and indigenous knowledge is required, but no comprehensive list of the useful local plants is available. Thus, in this work, we assess (1) their diversity and phytogeography; (2) the role of geophysical, historical, and socio-economic factors on species distribution and uses; and (3) potentially relevant species for sustainable development. Data were obtained from flora, scientific publ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…These climatic factors and the particular orography (mainly altitude and exposure to prevailing winds) of each island enable a variety of mesoclimates that are reflected in the high diversity of habitats and ecological conditions and, consequently, in the distribution of the approximately 750 spontaneous vascular plant taxa (native or introduced) that occur in this archipelago (Duarte et al, 2022) and, also, in the wide diversity of plant communities found in these islands, including the predominant grasslands, which range from the xeric in the arid lowlands to the more mesic in high-altitude areas (Figure 1B-D), woodlands, and shrublands in the more humid mountainous zones (Romeiras et al, 2015). The growing human population on the islands, which increased threefold in the last decades-184,999 in 1950decades-184,999 in to 598,682 in 2023decades-184,999 in (Macrotrends, 2023-exerts strong anthropogenic pressure on plant communities, posing major challenges for the conservation of natural resources (Romeiras, Catarino, Gomes, et al, 2016).…”
Section: Study Areamentioning
confidence: 99%
“…These climatic factors and the particular orography (mainly altitude and exposure to prevailing winds) of each island enable a variety of mesoclimates that are reflected in the high diversity of habitats and ecological conditions and, consequently, in the distribution of the approximately 750 spontaneous vascular plant taxa (native or introduced) that occur in this archipelago (Duarte et al, 2022) and, also, in the wide diversity of plant communities found in these islands, including the predominant grasslands, which range from the xeric in the arid lowlands to the more mesic in high-altitude areas (Figure 1B-D), woodlands, and shrublands in the more humid mountainous zones (Romeiras et al, 2015). The growing human population on the islands, which increased threefold in the last decades-184,999 in 1950decades-184,999 in to 598,682 in 2023decades-184,999 in (Macrotrends, 2023-exerts strong anthropogenic pressure on plant communities, posing major challenges for the conservation of natural resources (Romeiras, Catarino, Gomes, et al, 2016).…”
Section: Study Areamentioning
confidence: 99%
“…The climatic conditions of Cabo Verde were shown to be adequate for Faidherbia albida, but, the present distribution of this tree is restricted to fairly small patches, which does not reflect its potential climatic niche. The land use of Cabo Verde underwent significant changes during human settlement (Duarte et al, 2022). Mainly intensive agricultural practices, and many introduced species have cleared a large portion of native tree populations (Monteiro et al, 2020;Varela et al, 2022).…”
Section: Effect Of Lulcmentioning
confidence: 99%
“… * Bibliographic sources and online databases on medicinal applications of Cabo Verde’s studied species [ 12 , 19 , 31 , 33 , 34 , 35 , 36 , 37 ]. ** Plant parts used in the present study.…”
Section: Figurementioning
confidence: 99%
“…Several medicinal plants were introduced in Cabo Verde, mainly by immigrants of different ethnic groups from the West African regions [ 11 ]. The use of these plants to treat various diseases still constitutes an important health resource with significant potential for research and development of new medicines [ 12 ].…”
Section: Introductionmentioning
confidence: 99%